Doping‐Assisted Phase Changing Effect on MoS2 Towards Hydrogen Evolution Reaction in Acidic and Alkaline pH. Issue 1 (16th January 2020) - Bolar, Saikat; Shit, Subhasis; Murmu, Naresh C.; Kuila, Tapas
Abstract: Hydrogen evolution reaction (HER) was improved through nitrogen (N) doping in molybdenum disulfide (MoS2 ) due to the formation of 1T‐metallic phase as compared to the thermodynamically stable 2H‐semiconducting phase. Generally, the phase transition of MoS2 from semiconducting 2H to metallic 1T was carried out by chemical intercalation method. A facile solvothermal synthetic procedure is used to organize 1T@2H MoS2 nanoflower by incorporating N in MoS2 crystal lattice which improved the catalytic activity with the generation of metallic property of MoS2 . Optimized N doping is an effective strategy for the development of mixed phase MoS2 . Physicochemical characterization techniques confirmed the formation of hybrid phase (1T@2H) MoS2 by N incorporation. A tuned dopant concentration in MoS2 crystal lattice effectively enhanced the catalytic performance by modifying the physical and chemical properties. Moreover, optimal N doped MoS2 offered a very low overpotential of ∼108 and ∼141 mV to reach the benchmarking current density of 10 mA cm −2 for HER in acidic and basic medium, respectively. This work elucidated a rational implantation of phase engineering, which is an efficient strategy to develop efficient electrocatalysts, shedding light on the improvement of transition metal‐based electrocatalyst in renewable energy technologies. Abstract : A hybrid catalyst : An effective engineering strategy was developed to prepare 1T@2H hybrid phase MoS2 by N‐doping on its 2H phase. The doping strength is the key factor for the construction of mixed phase system in a precise way. Optimized phase transition is characterized by physicochemical techniques. A novel approach is developed to explore robust electrocatalyst with high HER activity in dual pH medium.